Prevalence of Electrolyte Imbalance in Hypoxic-ischemic Encephalopathy: A Hospital-based Prospective Observational Study - Jehangir Allam Bhat; Sajad Ahmad Sheikh; Roshan Ara (Mashhad University of Medical Sciences, 2019)
Background: The present study aimed to investigate the prevalence of electrolyte imbalance in hypoxic-ischemic encephalopathy (HIE). Moreover, the correlation of this condition with Apgar score is evaluated. Methods: This prospective observational hospital-based study was conducted on 75 neonates affected by asphyxiation. Immediately (within ≤ 30 min of stabilization) after resuscitation, basic routine tests along with sodium (Na+), potassium (K+), and calcium (Ca++) were requested from laboratory to be quantitatively estimated. These neonates were clinically examined and classified into various stages of HIE according to recommended staging classification.  The values of electrolytes were calculated and compared between various stages of HIE. Furthermore, the correlation between these electrolytes and Apgar score was assessed. Results: It was observed in our study that HIE is associated with low levels of sodium and calcium. On the other hand, it is correlated with high levels of potassium. As severity of HIE increases, sodium and calcium levels decrease, while potassium level augments. Apgar score was significantly correlated with sodium and potassium. However, the correlation of potassium and sodium with Apgar score was shown to be negative and positive, respectively. Calcium levels did not have a significant correlation with Apgar score. Conclusion: Electrolyte imbalances, such as hyponatremia, hyperkalemia, and hypocalcemia are common in HIE. Hyponatremia and hyperkalaemia are significantly correlated with Apgar score. Therefore, Apgar score can be used as a determinant to start electrolyte therapy in HIE.